Segregation At Pondok Pesantrens In Kota Banjarmasin, South Kalimantan - Inna Muthmainnah (AIUA Journal of Islamic Education, 2019)
The two reasons of this study were the scanty prior studies concerning segregation at pondok pesantren and the fact that during my dissertation research I found that different pondok pesantrens applied segregation differently. The previous studies suggested that a leader employed segregation in accordance with the type of his educational background. By contrast, in this study I argued that the segregation implemented was the opposite type of their previous education as a sort of reflection. The objectives of the study were to explore the leaders’ views at pondok pesantrens in Kota Banjarmasin on segregation; to discover the arguments of the leaders’ views; and to describe the segregation implemented. This study employed a qualitative case study by employing interview, observation, and documentation methods to triangulate the data which was analyzed through content analysis. The leaders, the ustadzs, the ustadzahs, and the santris at three pondok pesantrens were involved in this study. This study found that the leaders were in different views; two viewed that the santris should be segregated while the other viewed the opposite. The argument of first view was the Qur’anic verses and hadith. The implementation was in the line with the leaders’ views. The two leaders in the first view segregated their santris; the first segregated the santri completely in all aspects of teaching and learning process, while the other segregated in teaching and learning process in class only. The leader in the second view did not segregate his santris, except in the activity of Zuhur prayer for the lack of space.